Emerging monitoring technologies to reduce illegal fishing activities at sea and prevent entry of fraudulent fish into markets - Willette, Demian A.; Ababouch, Lahsen; Barber, Paul H.; Bunje, Paul M. E.; Cauzac, Jean-Pierre; Conchon, Anna; Trenkel, Verena M. (Frontiers in Sustainable Food Systems, 2023)
National and global priorities are increasingly focused on the concurrent marine fisheries challenges of food security, illegal fishing, and declining fisheries resources. Molecular genetics and electronic monitoring technologies can advance solutions to these challenges, particularly in fisheries surveillance and seafood traceability. A growing number of studies continues to validate the utility of these tools. What is needed next is guidance to support their wider, more conventional adoption and implementation, either complementary to or in the absence of government policies. Here, we synthesize discussion held during the Borchard Foundation Colloquium held in July 2022 in Missillac, France on modernizing global fisheries with emerging technologies. Our aim is to provide perspectives to scientists, resource managers, and policy makers of emerging monitoring technologies, summarize the utility of these technologies in fisheries, and conclude with how the objective to modernize global marine fisheries is a prime opportunity to engage fresh talent in a new era of fisheries innovation.